A comparative study of radiometrically observed and numerically computed infra-red fluxes (MAUSAM, 1972)
Infra-red radiative fluxes and cooling rates obtained from radiometer soundings made over Poona during 1963-66 have been compared with the results of computations using numerical methods.Good agreement has been noticed between the observed and computed values of the upward flux. The nature of variation with height and season of the ob36rved and computed downward flux is found to be similar. However, at any level, the absolute value of the observed downward flux is higher than the computed one by 75 to 150 ly/day. The differences between the observed and computed values of the cooling rate are small in the troposphere.